Environmental Resilience Challenges and Mining Policy in East Kutai Regency, Indonesia: A Case Study - Ignasius Dwi Oktavianus; Muhammad Aswar; Muhammad Hairul Saleh; Zahra Ahmadi (Dealings Foundation Institute, 2024)
This study aims to identify weaknesses in the oversight of excavation C mining activities by the East Kutai Regency Government, which contribute to soil degradation and alterations to natural landscapes. These mining operations result in large, water-filled pits that become breeding grounds for mosquitoes and disease, while also causing air pollution during the dry season. The research employs a qualitative approach, combining a literature review with interviews. The findings reveal that, first, excavation C mining disrupts ecosystem balance through the overexploitation of natural resources and fosters illegal mining activities. Second, challenges in monitoring excavation C mining involve the Satpol PP (Civil Service Police Unit) as the primary enforcement body, along with the enforcement of local regulations designed to minimize environmental damage. However, a lack of coordination between the East Kutai Regency Satpol PP and the East Kalimantan Provincial Police complicates regulatory enforcement and community protection efforts. This study recommends implementing strict sanctions against companies that illegally damage the environment to improve oversight effectiveness and promote environmental sustainability.